Serum soluble urokinase-type plasminogen activator receptor levels in male patients with acute exacerbation of schizophrenia. (28th February 2016) - Genc, Abdullah; Kalelioglu, Tevfik; Karamustafalioglu, Nesrin; Tasdemir, Akif; Genc, Esra Sena; Akkus, Mustafa; Emul, Murat
Abstract: Inflammatory abnormalities have been shown in the pathogenesis of schizophrenia. Soluble urokinase-type plasminogen activator receptor (suPAR) is a protein that is measurable in the circulating blood and reflects the inflammation in the body. We aimed to investigate serum suPAR levels in patients with schizophrenia who were in acute state and to compare with healthy controls. Forty five patients and 43 healthy controls were included in the study. We found no significant difference in suPAR levels between patients and controls, suggesting that suPAR as an inflammatory marker does not have a role in the inflammatory process of acute schizophrenia. Highlights: We investigated suPAR levels in schizophrenia patients and compared with controls. We found no significant difference in suPAR levels between patients and controls. suPAR does not have a role in the inflammatory process of acute schizophrenia.